Estudio de prefactibilidad para la instalación de una planta procesadora de mango deshidratado cubierto con chocolate - Mardini Burgos, Nayme Royina Faride (2020)
Today consume healthy products is becoming trendy, while around the 70s, buying a soda or a snack was a synonym of luxury, today there is more talk about the damages that they cause. However, no one can deny that it is difficult to leave those days behind and stop eating those delicious snacks; that is why this work presents a healthy alternative: dehydrated mango covered with chocolate. In the first chapter the main problems that society face: obesity, cardiovascular diseases, etc.; and proposes an attractive solution with the product. In the second chapter we will evaluate who the consumers will be, also their characteristics such as location, ability to pay for the product, behaviors and more. Faced with the results, an alternative price is proposed in comparison to existing competitors, with the same product or possible alternatives. Next, in the third chapter, a localization study was carried out, evaluating various factors in both macro-location and micro-location, in order to find the most convenient location of the production plant and offices. In the fourth chapter the size of the market, the capacity of the machines, the availability and quantity of resources and the equilibrium point to determine the size of the plant were compared. Then, in the fifth chapter, the technical specifications of the product were defined and the production process was described, establishing the machines involved in this, the number of operators required, the quality control that will be carried out from the receipt of inputs until the distribution of the product to the customer. The environmental impacts generated in each stage of the process or task elaborated by the operators were also analyzed, proposing in this way corrective measures to mitigate the impacts. In addition, a mapping of hazards and risks presented at each work station was prepared, the preventive maintenance plan for machines and equipment was established, the supply chain was designed and the production program was defined. Likewise, the requirements of inputs, raw materials and indirect workers were quantified to carry out the process. To finish this chapter, the layout of the plant was analyzed, that is, the physical areas and the 4 size required for each of them were determined, the plan of the plant was designed and the project schedule was determined to put it into operation. Subsequently, in chapter six, the company was specified along with its mission and vision. Also, the requirement of management, administrative and service workers was specified and the functions and profile for each job position were established. Additionally, the organization chart of the company was prepared. Finally, in chapter seven, long-term investments of tangible and intangible assets and short-term assets such as working capital were estimated. Production costs, sales revenue budgets, operating costs and expenses budgets, financial budgets (debt service, income statement, balance sheet and economic and financial funds flow) were quantified in detail. The project was evaluated economically through the analysis of indicators, ratios and sensitivity of the project.